PENGARUH KETERAMPILAN, PENGALAMAN KERJA DAN GAYA KEPEMIMPINAN MANDOR TERHADAP PRODUKTIVITAS TENAGA KERJA PEMANEN NANAS (PT GREAT GIANT PINEAPPLE DEPARTEMEN PLANTATION GROUP 4) - Wayan Astika Darmayanti; Wuryaningsih Dwi Sayekti; Raden Hanung Ismono (Lampung University, 2021)
The aims of this research were to study the level of nutritional status, work skills, work experience, and foreman leadership style as well as its effect on the productivity of pineapple harvesting labor in PT Great Giant Pineapple Department Plantation Group 4. The research is conducted by surrvey method at PT Great Giant Pineapple Department Plantation Group 4,Labuhan Ratu Sudistrict, East Lampung Regency. Data is collected in August-September 2019. The total respondent for this research are 50 workers are chosen by purposive method. Analyzed by quantitative descriptive and multiple linear regression. The result of this research showed the level nutrition status of labor was normal with good work skills, work experience of less than a year, the leadership style applied was democratic and level of labor productivity was moderate. The laor productivity was influenced by skills, work experience, foreman leadership style, age and education.Keywords : experience, foreman, nutritional status, productivity, skills.